ENHANCING STUDENTS’ VOCABULARY MASTERY THROUGH WORDS HUNTING GAME OF THE FIFTH GRADE - Indah Majidah (Edulitics (Education, Literature, and Linguistics) Journal, 2017)
In this study, the researcher used quasi-experimental and observe the fifth grade of MI AL-HUDA Sumberagung. As the population is all of fifth grade and the sample consist of 23 students. The data of this study are taken from test, questionnaire, and observation. For collecting data, the researcher gives pre-test, treatment and post-test. The writing tests consist of 20 test items. The result of the study proves that the hypothesis is accepted, it can be seen from the result of t-test 3.09 it is higher than t-table 2.81 at levels significance 0.01 with d.f 22. It means that there is significant differences between students who are teach before using words hunting game and after using words hunting game in increasing vocabulary mastery. The problem statements in this research are 1) the effectiveness of using words hunting game to increase the students’ vocabulary mastery at fifth grade of MI AL-HUDA Sumberagung in the academic year 2017/2018, and 2) the students’ response toward the using of words hunting game to increase the students’ vocabulary mastery at fifth grade of MI AL-HUDA Sumberagung in the academic year 2017/2018.